Board structure-performance relationship in microfinance institutions (MFIs) in an emerging economy. Issue 5 (3rd October 2016) - Thrikawala, Sujani; Locke, Stuart; Reddy, Krishna
Abstract : Purpose: The purpose of this paper is to investigate the relationship between board structure, financial performance and outreach of microfinance institutions (MFIs) in Sri Lanka, using unbalanced panel data for 300 MFI-year observations for the period 2007 to 2012. Design/methodology/approach: Empirical research relating to governance practices in MFIs is still in its infancy, and further studies are needed to determine how improved governance practices may enhance sustainability and outreach of MFIs, especially in emerging economies. The authors use regression techniques to examine whether board structure has an influence on MFI performance. Findings: After controlling for internal corporate governance variables, regulatory status, size, age, leverage and year effects, the authors report that board structure does contribute to the financial performance and outreach of MFIs in Sri Lanka. Research limitations/implications: The availability of data in the public domain captures the major MFIs but does constrain the generalisability of findings. Practical implications: This study enables individual MFIs to evaluate potential restructuring of their boards to promote a dual mission and achieve a more accelerated economic development. Social implications: The findings may encourage policy makers to promulgate policy guidelines to deepen MFI outreach to the poorest people. Originality/value: Inconsistent findings in prior studies and a general lack of empirical results for the microfinance industry have led to an unclear message regarding corporate governance and MFI performance. This study fills the research gap, contributing to the existing corporate governance literature in the microfinance sector and providing evidence from an emerging economy.